TET2 mutation in acute myeloid leukemia: biology, clinical significance, and therapeutic insights - Qiang Gao; Kefeng Shen; Min Xiao (Clinical Epigenetics)
Abstract TET2 is a critical gene that regulates DNA methylation, encoding a dioxygenase protein that plays a vital role in the regulation of genomic methylation and other epigenetic modifications, as well as in hematopoiesis. Mutations in TET2 are present in 7%–28% of adult acute myeloid leukemia (AML) patients. Despite this, the precise mechanisms by which TET2 mutations contribute to malignant transformation and how these insights can be leveraged to enhance treatment strategies for AML patients with TET2 mutations remain unclear. In this review, we provide an overview of the functions of TET2, the effects of its mutations, its role in clonal hematopoiesis, and the possible mechanisms of leukemogenesis. Additionally, we explore the mutational landscape across different AML subtypes and present recent promising preclinical research findings.